Perspective of Clinical Nurses on Facilitating Factors and Obstacles of Conducting Research and Implementation of Its Results - Seyed Hamid Seyed Bagheri; Hadi Khoshab; Hossein Rafiee; Abbas Abbaszadeh; Fariba Borhani (Golestan University of Medical Sciences, 2016)
Background: Participation of nurses in research studies is a requirement of achieving evidence-based nursing, but studies in this regard are limited. This study aimed to determine the viewpoints of nurses regarding the facilitating factors and obstacles of participating in research and utilization of its results in clinical practice. Methods: This descriptive study was done in 2013 at teaching hospitals affiliated to Kerman University of Medical Sciences. Study subjects included 210 clinical nurses with at least a bachelor's degree who were selected by stratified random sampling method. Data collection tools included a researcher-made 3-section questionnaire. The first section consisted demographic information and the second and third sections contained 21 questions each that evaluated the motivational factors and obstacles of research, respectively. Data were analyzed using descriptive statistics (mean and standard deviation). Results: Of all the participants, 87.6% were female with average age of 38.08 ± 4.93 years. Regarding the research facilitating factors, the highest score was given to the intrinsic interest for knowledge acquisition and increased practical work ability. In this section, the lowest scores were given to interaction with other colleagues and the existence of competitive conditions. In terms of the research obstacles, the highest scores were reported for problems at work including staff shortages and high workloads, while the lowest scores were reported for low self-confidence and lack of interest and unwillingness to do research. Conclusion: The results of this study can provide information for nursing policymakers to establish measures that constructively motivate nurses to do research and utilize its results by the managers.